ANALISIS PERILAKU PENGETAHUAN DALAM INGATAN MELALUI JAWABAN PRE-TEST, POST-TEST DAN KUISIONER MONITORING I-II PESERTA PELATIHAN VOKASIONAL RENCANA USAHA DAN MANAJEMEN KEUANGAN KELOMPOK SWADAYA MASYARAKAT (KSM) BINAAN BUSINESS DEVELOPMENT CENTER (BDC) SRIW - Thoyib, Ellys; Effendi, R.Y. (Fakultas Ekonomi Universitas IBA, 2018)
The KSM pre-test and post-test vocational training and monitoring questionnaire aimed to determine the extent of KSM's understanding of the material of the Business Plan and Financial Management before and after KSM vocational training. Understanding of training material can be said as knowledge that is responded to by the eyes, the participants' hearing and feelings will then be interpreted and understood in the mind then settles in the memories of participants (J. Paul Peter & Peter C. Jackson, 2009). Knowledge in participants' memories is so dynamic that it can be said to be a behavior, that is knowledge behavior in memory. Knowledge behavior in this memory was examined through the value of the answers to the pre-test, post-test and training participants I and II questionnaires. The number of participants is 70 KSM, but 43 KSMs will be studied and the same people will take part in the pre-test, post-test and monitoring questionnaire I and II. Knowledge behavior in memory is analyzed through the dynamics of the answers to the pre-test to post-test and monitoring I to II. Groups that experience an increase in value are said to be Knowledge Behavior in Memory with Positive Mode and groups that experience impairment are called Negative Modes and groups with stable values are called Consistent Modes. Groups that experience an increase in value are said to be Knowledge Behavior in Memory with Positive Mode and groups that experience impairment are called Negative Modes and groups with stable values are called Consistent Modes. Reward and punishment in the form of periodic and intensive guidance and administration sanctions. Reward and punishment in the form of periodic and intensive guidance and administration sanctions